Does Husband Support Associated with the Duration of Breastfeeding? - Pratiwi, Bintang Agustina; Lesmi, Anisa; Husin, Hasan; Angraini, Wulan; Suryani, Desri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Breastfeeding coverage in the Bengkulu ranks second lowest (68.9%) in Indonesia. The husband is the closest person mother who can support successful breastfeeding up to 2 years. This study aimed to examine the effect of husband support on the duration of breastfeeding. Subjects and Method: This was a cross sectional study. A sample of 44 fathers who had children aged 2-3 years in Lingkar Barat community health center, Bengkulu, was selected for this study. The dependent variable was breastfeeding duration. The independent variable was informational support, assessment support, instrumental support and emotional support. Data collection using a valid and reliable questionnaire. Data analysis was performed using multiple linear regression. Results: The results showed the informational support (b= 0.37; 95% CI= -0.07 to 0.75; p= 0.046), apprisial support (b= 0.29; 95% CI= -0.39 to 0.98; p= 0.393), and instrumental support (b= 0.43; 95% CI= -0.18 to 1.05; p= 0.161) were positively associated with the duration of breastfeeding. Emotional support was negatively associated with the duration of breastfeeding (b= -0.37; 95% CI= -1.03 to 0.29; p= 0.252). Conclusion: Husband's support is associated with length of breastfeeding.